Diversity and Potential of Macroscopic Fungi in the Caldera of Mount Tujuh Lake, Kerinci Seblat National Park, Jambi - Andesmora, Evan Vria; Yulio Saputra, Dalli (Jurnal Hutan dan Masyarakat, 2025)
Kerinci Seblat National Park (TNKS) is a biodiversity hotspot in Indonesia, yet studies on macroscopic fungi in this area remain limited. This research explored the biodiversity and potential utilization of macroscopic fungi in Gunung Tujuh Resort, Kerinci Regency, Jambi. Field sampling was conducted in August 2023 using an opportunistic sampling method, and identification was based on macroscopic morphological characteristics. A total of 15 fungal species belonging to 11 families, 4 orders, and two classes were identified. Most species (14) were classified under the phylum Basidiomycota, while one species belonged to Ascomycota. The identified species include Laccaria sp., Hygrocybe sp., Galerina marginata, Marasmius sp. (four species), Meripilus sp., Collybia sp., Armirallia sp., Schizophyllum sp., Amauroderma rugosum, Mycroporus sp., Russula sp., and Xylaria sp.. Interviews and literature studies revealed that these fungi have not been utilized by the local community. Given the high fungal diversity and the potential risk of biodiversity loss, further studies on the ecological roles and possible utilization of macroscopic fungi in the region are necessary.